Bodily movement of canines by removable orthodontic appliances - M. Shirazi (Journal of Dental Medicine, 1987)
Canine retraction to the place of extracted premolar is a basic step in the majority of orthodontic treatments. This is performed frequently by incorrect axis change of canine which moves its root anteriorly. This study is aimed to evaluate canine bodily movements by removable orthodontic appliances and describing the steps of an ideal orthodontic treatment as well as discussing important points on canine retraction. 4 patients with treatment plan of extracting first premolar and replacing the space by canine movement were selected and simple orthodontic appliance were delivered to them. Radiographic analysis showed pdl increased continuously in the side of force application which confirms bodily movement of tooth. Besides, chair side time  is less for removable appliances. Therefore, removable systems are the most desirable orthodontic treatments although there are some limitations in their application.